Bioaugmentation and phytoremediation of heavy metal from leachate contaminated soil / Jayanthi Barasarathi - Jayanthi , Barasarathi (2018)
Environment contaminated with heavy metals pose a significant problem, mainly due to the toxic effects of these metals throughout the food chain. Landfilling contributes to high volume of leachate generation. In Malaysia, the daily generation of leachate from landfills is about 6 million litres. Landfill leachate is highly heterogeneous and contains heavy metals. Improper waste management allows lateral flow of leachate into soil and cause serious contamination and it later reaches surface and groundwater sources. This posed risks to human health and the environment. Therefore, it is necessary to find solution for the removal of heavy metal from metal contaminated soil. This study aimed to characterize soil and leachate of two selected landfills in Malaysia and further isolate, identify and screen potential microbes for the removal of heavy metals from leachate contaminated soil. The microbes were then formulated into seven different treatments for bioaugmentation of leachate contaminated soil. The effect of inoculum concentration was also evaluated while the field trials were conducted using the best consortia. Phytoremediation to remove heavy metals from the leachate contaminated soil was also carried out using four different plant species. Characterization of both landfill soil and leachate indicated that Pb, Cu, Al, As, Mn, Cr, Zn, Fe and Ni contents were higher than the prescribed limits. Eighteen bacterial species were isolated from the leachate contaminated soil and were further screened for heavy metal sensitivity using the clear zone method. Among the isolates, Burkholderia vietnamiensis demonstrated the highest tolerance for metals (>20ppm). The best remediation results on soil collected from Taman Beringin landfill showed the reduction of 61%, 87%, 47%, 75%, 59% and 61% for As, Al, Mn, Fe, Ni and Cr, respectively by Proteo-bacteria group. Similarly, Proteo-bacteria also removed Al (87%), Mn (49%), Cu (65%), Fe (86%), Ni (78.7%) and Cr (67%) from soil from Bukit Beruntung Landfill. Increasing the inoculum concentration from 10% to 30% v/w showed increased capacity of metal removal from the contaminated soil. Results from the 100 days field trials at Taman Beringin landfill revealed that significant reduction of Pb, Mn, Fe, Al, Cu, Cr and Zn occurred when proteo-bacteria consortia was administered to the contaminated plots. The metal concentration was much lower in the microbe amended plots as compared to control plots. Phytoremediation studies revealed that Cordyline sp. is the most promising plant and the highest percentage of removal was was for Cu (94.35%), Pb (63%), Ni (88.9%), As (85%), Zn (77.55%), Cr (75%) and Al (67.5%) from the soil collected from Taman Beringin Landfill. For phytoremediation of contaminated soil from Bukit Beruntung Landfill, Tradescantia spatachea was the most prominent species with the highest percentage of metal removal for As (87.7%), Cu (81.5%), Fe (48.5%) and Chlorophylum comosum for Al (60%), Zn (73%), Cr (54%) and Pb (78.6%). Hence, bacterial isolates, especially those that belong to Proteo bacteria showed higher metal removal from contaminated soil, while Cordyline sp., T. Spatachea and C. comosum have high potential to be used for phytoremediation of heavy metal.